O lixo como passivo ambiental e a Política Nacional de Resíduos Sólidos: os potenciais impactos e desafios da cidade de Castanhal/Pará - PINHEIRO, Adson Caxias (2019)
Lack of solid waste management is becoming a problem for managers of Brazilian municipalities. This is happening due to the large expansion of urban areas and, consequently, due to increased consumption. Improper accumulation of solid waste has been increasing constantly, therefore, they are dropped thousands of tons of "waste" daily in places known as "dumps". This is a reality experienced not only by the Castanhal city as well as by most municipalities. As a result, this study aims to evaluate the potential impacts and challenges, environmental and social, to the city of Castanhal / Pará regarding the suitability of the municipality to changes and deadlines imposed by Law 12,305 / 10. Specifically, this work is to present the way the municipality is managing solid waste and confronting with the legal instruments and requirements and technical standards. The methodology chosen in the research is classified as exploratory, descriptive, besides the technical methodology of preparation of an environmental impact matrix, with the universe the city of Castanhal. The main results indicate that the collection of waste is not made appropriately. Dumpsites, both the Pantanal as of May 1 are already on the edge, with the need for new strategies to remedy the problem. The suggestion of the most suitable currently used for final solid waste disposal facilities are discussed.